Retrans: Regional Language-English Translator Machine Based on Artificial Intelligence (AI) for The 10 New Bali Regions - Naufal Siddiqi Nasrullah; Griselda Gian Heris Herdina; Nurul Aini (Proceeding International Conference on Religion, Science and Education, 2023)
This study aims at scrutinizing the productivity of translation communication media as an intermediary for information exchange needs to be significantly improved, more in the middle of the era of the industrial revolution 4.0 which enroll automation and data exchange using the internet in the process of search websites, data and information analysis and cloud services. This is in line with the current era of technology 5.0 which brings big impact in all lines of life. Such facilities can be integrated into innovation of Regional Language-English translation machine, it can be enhanced through innovation of machine translation based on artificial intelligence (AI), the one of innovation based on AI is RETrans, to assist foreign tourists and local residents in building effective communication when visiting the 10 new Bali area. This research discusses the innovation based on integration between learning English and the sophistication of AI which will have advantages over previous teaching techniques. The article limits to discuss about how this AI system operates to apply machine translation specifically in 10 new Bali regions. This research discusses innovation from machine translation platforms to integrate machine translation media with AI sophistication.